Outcome of acute myeloid leukemia patients with pulmonary nodules of uncertain etiology receiving allogeneic hematopoietic progenitor cell transplant. (17th April 2015) - Lim, Sara J.; Lim, Matthew J.; Raptis, Anastasios; Hou, Jing‐Zhou; Farah, Rafic; Marks, Stanley; Im, Annie; Dorritie, Kathleen; Sehgal, Alison; Agha, Mounzer; Lim, Seah H.
Abstract: Pulmonary nodules (PNs) develop frequently in patients with acute myeloid leukemia (AML). They are of infectious or inflammatory origin. They pose potential challenges to successful hematopoietic progenitor cell (HPC) transplant as they may be niches for infection reactivation or sites susceptible to subsequent infections. We retrospectively analyzed the outcome of 20 AML patients with multiple PNs who underwent allogeneic HPC transplants (12 related, 8 unrelated). There were 13 males and seven females (median age 52 yrs). Nine patients were in CR1, seven in CR2, and four with residual disease. The median times from appearance of PNs and from last positive CT scans to transplant were three and two months, respectively. The median time from pretransplant CT scans to transplant was one month. Multiple PNs were still reported in 5/20 of the pretransplant scans. The PNs in all five patients did not worsen after transplant. Four patients (one with positive pretransplant CT scan) died within the first 100 d after transplant, but none from primary pulmonary pathology. The median survival of this group of patients was 350 d. Our results, therefore, suggest that multiple PNs of uncertain etiology in patients with AML do not impact adversely on the outcome of allogeneic HPC transplant.